Relational aspects of regulating clinical work: examining electronic and in-person compliance mechanisms. Issue 3 (20th October 2021) - Bajpai, Kartikeya; Chown, Jillian; Astik, Gopi; Green, Kristine
Abstract : Background: Clinical documentation quality is an important way to facilitate clinical communication, improve patient safety metrics and optimise hospital coding and public reporting. However, the monitoring of clinicians by external individuals (ie, those outside the profession or emanating from outside clinical teams) raises difficult questions relating to the autonomy of clinicians and an organisation's control over clinical work. Typically, documentation improvement initiatives have relied solely on electronic monitoring systems to vet clinician documentation. In such systems, quality personnel monitor clinical documentation and, on encountering potentially problematic content, use an electronic querying system to ask the clinicians to voluntarily clarify or modify the text if appropriate. Importantly, clinicians retain their professional autonomy and can choose to disagree with documentation requests. The current study empirically examines a clinical documentation improvement program which takes a different approach. This programme uses two modes of querying clinicians: (1) conventional electronic documentation clarification queries and (2) in-person verbal documentation clarification requests. Methods: We conducted regression analyses using archival documentation query data (n=19 650) from an American teaching hospital to compare the efficacy of conventional electronic documentation clarification queries and in-person verbal documentation clarification requests. Our dependent variable is the length of time between the documentation clarification request and the resolution of the query (ie, the time until a clinician responds). Findings: Our analyses demonstrate that in-person verbal documentation clarification requests are associated with a 30-hour reduction in the time it takes for a query to be resolved relative to electronic-only queries. Practical implications: The results suggest that while electronic regulatory systems might afford hospitals with opportunities to scale quality initiatives in a cost-effective manner, organisational efforts to influence clinical work may yet benefit from the human touch of in-person regulator–clinician interaction. Furthermore, the replacement of in-person compliance interactions with digital compliance requests can potentially produce negative compliance outcomes.